Implementation of Digital Anthropometry for Real Time Toddlers Nutrition Status at Balongdowo Village Posyandu - Triwiyanto, Triwiyanto; Luthfiyah, Sari; Hamzah, Torib; Utomo, Bedjo; Lamidi , Lamidi; Setyobudi, Sugeng Iwan; Julianto, Jusuf; Rosari, Angela Erti Suci (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
The current web page context is a research article that discusses the implementation and evaluation of a digital anthropometry device for the early detection of stunting in children under five years old in a rural village in Indonesia. The aim of the study was to apply a technology-based solution to overcome the challenges of measuring height and weight of children, as well as to provide timely and actionable information for the prevention and reduction of stunting. The contribution of the study was to demonstrate the feasibility and effectiveness of a community service program that integrated education, empowerment, and technology components to address the stunting problem in a local context and need. The method of the study involved a mixed-methods design, which combined quantitative and qualitative data collection and analysis, to evaluate the impact and outcomes of the digital anthropometry device and the community service program. The result of the study showed that the program improved the knowledge and awareness of stunting among the mothers and the cadres, as well as their skills in using the digital anthropometry device. The program also reduced the stunting cases and increased the nutritional status among the children, as indicated by the z-score indicators. The conclusion of the study was that the program was successful in achieving its objectives and outcomes, but also faced some challenges and limitations, such as the limited availability of the device, the technical difficulties in operating and maintaining the device, the low participation and compliance of some mothers and children, and the lack of follow-up and evaluation after the program ended